Fine-Tuning Oligodendrocyte Development by microRNAs - Lu, Richard; Barca, Olga (Frontiers in Neuroscience, 2012)
Myelination of axons by oligodendrocytes in the central nervous system is essential for normal neuronal functions. The failure of remyelination due to injury or pathological insults results in devastating demyelinating diseases. Oligodendrocytes originate in restricted regions of the embryonic ventral neural tube. After migration to populate all areas of the brain and spinal cord, they undergo a temporally well-defined series of molecular and structural changes, ultimately culminating in the cessation of proliferation, and the elaboration of a highly complex myelin sheath. The emergence of microRNAs as potent regulators of gene expression at the post-transcriptional level has broad implications in all facets of biology. Recent studies have demonstrated a critical role of microRNAs in oligodendrocyte development, including cell proliferation, maturation, and myelin formation. In this review, we will highlight and discuss the recent understanding of functional links of miRNAs to regulatory networks for central myelination, as well as perspectives on the role of miRNAs in demyelinating diseases.